Congenital Generalized Lipoatrophy (Berardinelli-Seip Syndrome) Type 1: Description of Novel AGPAT2 Homozygous Variants Showing the Highly Heterogeneous Presentation of the Disease - Ceccarini, Giovanni; Magno, Silvia; Pelosini, Caterina; Ferrari, Federica; Sessa, Maria Rita; Scabia, Gaia; Maffei, Margherita; Jéru, Isabelle; Lascols, Olivier; Vigouroux, Corinne; Santini, Ferruccio (Frontiers in Endocrinology, 2020)
Berardinelli-Seip congenital lipoatrophy (BSCL) is characterized by near total fat atrophy, associated with the progressive development of metabolic complications. BSCL type 1 (BSCL1) is caused by mutations in AGPAT2, encoding 1-acylglycerol-3phosphate-O-acyltransferase  (recently renamed lysophosphatidic acid acyltransferase beta), which catalyzes the transformation of lysophosphatidic acid in phosphatidic acid, the precursor of glycerophospholipids and triglycerides. BSCL1 is an autosomal recessive disease due to AGPAT2 pathogenic variants leading to a depletion of triglycerides inside the adipose organ, and to a defective signaling of key elements involved in proper adipogenesis. We herein investigated the characteristics of two AGPAT2 variants in Caucasian Italian patients with Berardinelli-Seip congenital lipoatrophy. The first patient exhibited a novel homozygous nonsense c.430 C>T AGPAT2 mutation (p.Gln144*) predicting the synthesis of a truncated enzyme of approximately half of the proper size. The second patient harbored a homozygous AGPAT2 missense variant (p.Arg159Cys), never described previously in BSCL1 patients: the segregation of the disease with the mutation in the pedigree of the family and the in silico analysis are compatible with a causative role of the p.Arg159Cys variant. We remark that BSCL1 can be clinically very heterogeneous at presentation and that the associated complications, occurring in the natural history of the disease, reduce life-expectancy. We point to the necessity for medical treatments capable of reducing the risk of cardiovascular death. In BSCL1 patients, the assessment of cardiovascular disease with conventional diagnostic means maybe particularly challenging.